India : Rajasthan, State Financial Accountability Assessment - World Bank (Washington, DC, 2012)
The primary purpose of this study is to support the reform efforts of the Government of Rajasthan through identifying specific opportunities for more effective financial management and control over public resources. The study was undertaken based on consultations with the Principal Secretary Finance Department and in conjunction with the economic analysis undertaken by the World Bank in Fiscal Year 2005 and the state's center for good governance. The study ranges over the different components of public financial management and accountability (PFMA) including budget preparation, approval and execution, internal control including internal audit, Government accounts and financial reporting, and external audit and legislative scrutiny. The study also covers the public access/right to financial information as an instrument of promoting transparency in and accountability of administration and gives recommendations.